Cabo Verde : Selected Issues Paper. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Selected Issues paper provides an overview of the nature and scope of corresponding banking relationships (CBRs) withdrawals in Cabo Verde and discusses policy options to address this challenge. The paper reports the results of a bank level survey and employs the minimum scope framework developed by Grolleman and Jutrsa (2017) on Cabo Verdean bank level data for 2014-2017. Banks in Cabo Verde have experienced a reduction in CBRs since 2013. Bank level survey shows that the terminations are broad based and involves both the central bank and commercial banks. The impact on the banking system has so far been minimal but banks reported facing increased cost of US dollar transactions. The results using the minimum scope framework shows that value of payment flows declined significantly between 2014 and 2016. There is a need for coordinated efforts by all relevant stakeholders at the institutional, national, and regional levels to contribute their knowledge and skills to the resolution of the problem.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet